2022
DOI: 10.1021/acscatal.2c00972
|View full text |Cite
|
Sign up to set email alerts
|

Surface Anchoring and Active Sites of [Mo3S13]2– Clusters as Co-Catalysts for Photocatalytic Hydrogen Evolution

Abstract: Achieving light-driven splitting of water with high efficiency remains a challenging task on the way to solar fuel exploration. In this work, to combine the advantages of heterogeneous and homogeneous photosystems, we covalently anchor noble-metal- and carbon-free thiomolybdate [Mo 3 S 13 ] 2– clusters onto photoactive metal oxide supports to act as molecular co-catalysts for photocatalytic water splitting. We demonstrate that strong and surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…[ 28 ] As shown in the reported MoS species, the valance states of Mo atoms in MoS 2 , Mo 2 S 12 2− , and Mo 3 S 13 2− cluster are all present as Mo 4+ (Figure S7, Supporting Information). [ 29,30 ] We proposed that the polymerization product of MoS 4 2− in our materials is a ‐MoS 3 . Further quantitative analysis of the peak areas showed that the ratio of Mo 5+ to Mo 4+ is about 2:1, which is consistent with the ratio of Mo 5+ to Mo 4+ in the crystal structure of a ‐MoS 3 (Figure 2e).…”
Section: Resultsmentioning
confidence: 94%
“…[ 28 ] As shown in the reported MoS species, the valance states of Mo atoms in MoS 2 , Mo 2 S 12 2− , and Mo 3 S 13 2− cluster are all present as Mo 4+ (Figure S7, Supporting Information). [ 29,30 ] We proposed that the polymerization product of MoS 4 2− in our materials is a ‐MoS 3 . Further quantitative analysis of the peak areas showed that the ratio of Mo 5+ to Mo 4+ is about 2:1, which is consistent with the ratio of Mo 5+ to Mo 4+ in the crystal structure of a ‐MoS 3 (Figure 2e).…”
Section: Resultsmentioning
confidence: 94%
“…However, effective charge separation and transfer remain decisive factors for photocatalytic hydrogen evolution activity. Various strategies (defect engineering, [4][5][6][7] morphological design, [8][9][10][11] heteroatom doping, [12][13][14][15] loading co-catalysts, [16][17][18] and construction of heterojunctions [19][20][21] ) have been proposed to overcome this pervasive problem present in photocatalysts. Appropriately designed heterostructures can improve the surface reaction kinetics of the catalytic system and thus significantly increase the carrier separation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…23 In recent years, [Mo 3 S 13 ] 2À has received increasing attention in many aspects such as hydrogen production and pollutant degradation due to its simple preparation method, low cost and excellent catalytic performance. 24,25 Additionally, [Mo 3 S 13 ] 2À as a co-catalyst has excellent stability in the electrocatalysis, 26 making it a promising nanomaterial. In this work, the shape of Co-MOF-74 can be easily controlled by changing the amount of [Mo 3 S 13 ] 2À (12.5 mg, 35 mg, 70 mg).…”
Section: Introductionmentioning
confidence: 99%